Hollywood and the culture elite how the movies became American - Decherney, Peter; Gale Group (New York Columbia University Press, 2005)
Explores how Hollywood and cultural institutions worked together, amid ethnic diversity, the rise of mass entertainment, world war, and the global spread of American culture, to insure their own survival and profitability and to provide a coherent, though shifting, American identity.
Electronic reproduction.
Keywords: Motion picture industry -- United States -- History; Motion pictures -- United States -- History; Motion pictures -- Social aspects -- United States; Culture in motion pictures; Electronic books; United States -- Social life and customs -- 20th century